(untitled) (Web of Teachers: Inderscience Research, 2024)
The State Museum of Remnants of the Victims of Qatagon was built at the Memorial of the Witnesses in Tashkent. Most of those who were slaughtered were jadides. The word "new" means "seeking innovation." So why the Shoor government was not pleased with the news promoters.